Molecular Epidemiological Investigation of Thalassemia in the Chengdu Region, Sichuan Province, Southwest China. (2nd November 2015) - Yu, Xia; Yang, Li-Ye; Yang, Hui-Tian; Liu, Cheng-Gui; Cao, Deng-Cheng; Shen, Wei; Yang, Hui; Zhan, Xiao-Fen; Li, Jian; Xue, Bing-Rong; Lin, Min
Abstract: Thalassemia is the most common inherited disease in southern China. However, this disorder is usually ignored by the health system in the Sichuan Province due to the lack of epidemiological data. To provide basic epidemiological data for thalassemia screening, genetic counseling, and prenatal diagnosis (PND) in the Chengdu region, a total of 3262 healthy subjects were assessed by complete blood count (CBC), reverse dot-blot gene chip, gap-polymerase chain reaction (gap-PCR), and PCR-DNA sequencing. A frequency of heterozygous thalassemia of 3.43% (112/3262) was found, of which 2.21% (72/3262) patients carried α-thalassemia (α-thal), 1.19% (39/3262) β-thalassemia (β-thal) and 0.3% (1/3262) hereditary persistence of fetal hemoglobin (Hb) (HPFH)/δβ-thalassemia (δβ-thal). Four types of α-thal mutations were found, the most prevalent being – – SEA (68.06%), followed by −α 3.7 (rightward deletion, 25.0%), Hb Quong Sze (Hb QS; HBA2 : c.377 T > C) (4.17%), and −α 4.2 (leftward deletion, 2.78%). The seven β-thal mutations included: codons 41/42 (−TTCT), HBB : c.126_129delCTTT (13/39, 33.33%); codon 17 (A > T), HBB : c.52 A > T (11/39, 28.95%); IVS-II-654 (C > T), HBB : c.316-197 C > T (9/39, 23.68%); −28 (A > G), HBB : c.–78 A > G (3/39, 7.69%); −29 (A > G), HBB : c.–79 A > G (1/39, 2.56%); codons 27/28 (+C), HBB : c.84_85insC (1/39, 2.56%), and the rare IVS-II-850 (G > T), HBB : c.316-1 G > T (1/39, 2.56%). Only one case of the Southeast Asian HPFH deletion was found. This is the first detailed molecular epidemiological survey of thalassemia in the Chengdu region, Sichuan Province, People's Republic of China (PRC).